Coolant temperature effect on gasoline engine - 555166 Alias Mohd. Noor; Rosli Abu Bakar; Srithar Rajoo; International Conference on Engineering and Technology (2001 : Brunei) (Skudai : Universiti Teknologi Malaysia, 2001)
20